2017
DOI: 10.7554/elife.21231
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the hypoxia-sensitive cells involved in amniote respiratory reflexes

Abstract: The evolutionary origins of the hypoxia-sensitive cells that trigger amniote respiratory reflexes – carotid body glomus cells, and ‘pulmonary neuroendocrine cells’ (PNECs) - are obscure. Homology has been proposed between glomus cells, which are neural crest-derived, and the hypoxia-sensitive ‘neuroepithelial cells’ (NECs) of fish gills, whose embryonic origin is unknown. NECs have also been likened to PNECs, which differentiate in situ within lung airway epithelia. Using genetic lineage-tracing and neural cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 106 publications
(206 reference statements)
3
43
0
Order By: Relevance
“…Having revealed growth stem cells at the tip of each filament, we explored whether different cell types had a dedicated or a common stem cell during post-embryonic growth. Previous experiments in zebrafish on labelling cell populations at early embryonic stages revealed that neuro-endocrine cells (NECs) are derived from the endoderm (Hockman et al , 2017), while pillar cells have a neural crest origin (Mongera et al , 2013). We followed a holistic approach to address the potency of gill stem cells once the organ is formed, by using inducible ubiquitous drivers to potentially label all possible lineages within a gill filament.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having revealed growth stem cells at the tip of each filament, we explored whether different cell types had a dedicated or a common stem cell during post-embryonic growth. Previous experiments in zebrafish on labelling cell populations at early embryonic stages revealed that neuro-endocrine cells (NECs) are derived from the endoderm (Hockman et al , 2017), while pillar cells have a neural crest origin (Mongera et al , 2013). We followed a holistic approach to address the potency of gill stem cells once the organ is formed, by using inducible ubiquitous drivers to potentially label all possible lineages within a gill filament.…”
Section: Resultsmentioning
confidence: 99%
“…Besides being the respiratory organ of fish, the gill has additional functions as a sensory and osmoregulatory organ (Sundin & Nilsson, 2002; Wilson & Laurent, 2002; Jonz & Nurse, 2005; Hockman et al , 2017). It contains oxygen sensing cells (Jonz et al , 2004), similar to those found in the mammalian carotid body although with a different lineage history (Hockman et al , 2017), and mitochondrial rich cells (MRCs) (Wilson & Laurent, 2002) that regulate ion uptake and excretion and are identified by a distinctive Na+, K+, ATPase activity. Other cell types include pavement cells (respiratory cells of the gills), pillar cells (structural support for lamellae), globe cells (mucous secretory cells), chondrocytes (skeleton of the filaments) and vascular cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our reporter and lineage tracing data documents a close developmental relationship between endoderm and the LPM. Expression of the key vertebrate endoderm gene sox17 demarcates prospective endoderm progenitors also in zebrafish Sakaguchi et al, 2006), as evident by the exclusive endoderm lineage-labeling with sox17:creERT2 ( Fig S1C) (Hockman et al, 2017). We detected sox17/drl reporter double-positive cells throughout gastrulation that begin to separate from each other from tailbud stage (Fig 2A-D).…”
Section: The Lpm As Early Established Specialized Mesodermmentioning
confidence: 73%
“…We also captured a cluster marked by Mpz and Plp1 , which are expressed in Schwann cells derived from the neural crest (Dyachuk et al, 2014;Espinosa-Medina et al, 2014;Feltri et al, 1999), as well as a small cluster distinguished by Snap25 , Ascl1 , Chga , which are molecular signatures for neuroendocrine cells (Nec) present in the adult mouse trachea (Montoro et al, 2018;Plasschaert et al, 2018) (Figures 1C and S1G). These Nec express transcription factors Phox2a and Phox2b required for cell fate specification in the parasympathetic ganglia ( Figure S1G) (Dyachuk et al, 2014;Espinosa-Medina et al, 2014), indicating that trachea Nec may originate from a lineage different from the pulmonary Nec found in the vertebrate lung (Hockman et al, 2017).…”
Section: Molecular Taxonomy Of Mesenchymal Cells Of the Developing Momentioning
confidence: 99%